AKAD JUAL BELI AKUN GAME ONLINE MOBILE LEGENDS MENURUT PANDANGAN ULAMA DI KOTA PONTIANAK - NIM. A1011181213, ARYA NUR MAHENDRA (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACK In this thesis, the author raises the problem of the Sale and Purchase Contract of Mobile Legends Online Game Accounts According to the View of Ulama in Pontianak City. According to the DSN MUI Fatwa Number 110 of 2017 concerning Sale and Purchase Agreements, objects or objects that are traded can be used according to Islamic law, meaning that the object is beneficial for oneself as well as for others. While online games themselves do not bring benefits in accordance with the syara' both for oneself and others, online games themselves are just a waste of time, one can be negligent and on the other hand can also cause harm to the users themselves. The formulation of the problem of this thesis is How is the Implementation of the Sale and Purchase Agreement for Mobile Legends Online Game Accounts According to the View of Ulama in Pontianak City? And thesis aims to find out data and information about the Sale and Purchase Contract of Mobile Legends Online Game Accounts and to express the Opinion of Scholars About the Implementation of the Sale and Purchase Contract of Mobile Legends Online Game Accounts. The type of research used is the Empirical Research method. This research is qualitative analysis with the intention of describing the existing situation using scientific research methods and solving problems based on data and facts that actually happened when this research was conducted. Collection of legal materials through interviews, observation and literature study. Based on the research conducted by the author, that selling Mobile legends online game accounts is the same as selling other goods that are sold through cyberspace or online. The seller posts or promotes the game account through online media such as Facebook, Instagram, or on online buying and selling sites. The Mobile Legends game account that is being traded is in the form of an ID and password which will be handed over to the buyer after the buyer makes a payment transaction. The price offered varies greatly depending on how many skins and other supporting attributes are in the Mobile Legends game itself. that apart from being a hobby of playing online games, sellers can benefit by trading Mobile Legends Online Game Accounts which can be a Factor Causing the Sale and Purchase Contract of Online Game Accounts., in the opinion of the MUI, there are 2 (two) legal consequences in buying and selling Mobile Legends Online Game Accounts, namely the consequences of Islamic law and the consequences of actions. The consequences of Islamic law are that they will be in sin and they will be in immoral acts so that it is difficult to repent because he is addicted, while the result of his actions is that he will feel dependence and negligence. in the opinion of the West Kalimantan Indonesian Ulema Council, it says that the Islamic view of buying and selling online game accounts is unlawful because the benefits generated are pseudo (temporary) benefits which make it unlawful because it only creates momentary pleasure and can cause many omissions.Keywords : Online Games, Buying and Selling, Majelis Ulama Indonesia, Contract, Mobile Legends. ABSTRAKPada skripsi ini, penulis mengangkat permasalahan Akad Jual Beli Akun Game Online Mobile Legends Menurut Pandangan Ulama di Kota Pontianak. Menurut Fatwa DSN MUI Nomor 110 Tahun 2017 mengenai Akad Jual Beli ialah benda atau objek yang diperjual belikan dapat dimanfaatkan menurut syariat Islam artinya benda tersebut bermanfaat untuk diri sendiri juga orang lain. Sementara game online sendiri tidak mendatangkan manfaat sesuai syara